Smart Moves: Internal and External Mobility in Malcolm X's and Barack Obama's Life-Writing - Šesnić, Jelena (2008)
My focus in part one will be on a classic of (Afro)-American autobiography, Malcolm X’ s 1965 record of his manifold moves, transgressions and boundary-crossings within his own community and outside of it. It can be argued that each of his migrations— and we need to remember that for African Americans mobility or the lack thereof has been a salient mark of group identity— portends also a shift in his identity make-up as we follow him moving from the country to the city, shuttling between various urban localities (the ghettoes of Boston and New York), experiencing a severe curtailment of the freedom of movement in prison simultaneously with his spiritual expansion and growth, which would culminate in his travels to Mecca and post-colonial Africa. In part two of my argument, I will examine textual self-representation undertaken by the first ever US black president, Barack Obama, in his 1995 memoirs Dreams from My Father, which is a staggering record of familial and personal mobility extending across several continents (the US mainland, Hawaii, Asia, Africa) and utterly compromising the rather clear-cut US nation-state racial and civic formations. The fact of the memoir’ s republication prompted by the momentum of a recently spectacularly closed presidential campaign, as well as the attendant repositioning of African American constituencies suggest perhaps a new mobility (be it social, political, geographic or psychological) available to or claimed by the black man in the USA nowadays.